The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1590/s0034-70942007000200001
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos adversos do sufentanil associado ao anestésico local pelas vias subaracnóidea e peridural em pacientes submetidas à analgesia de parto

Abstract: Subarachnoid or epidural sufentanil, in the doses used in this study, associated with local anesthetics, had the same effect on the duration of labor after analgesia and in the Apgar score of newborns. Sedation was the most frequent side effect in patients receiving epidural sufentanil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In addition to the inhibitory effects on cardiovascular and respiratory systems, sufentanil-induced gastrointestinal adverse effects, skin pruritus, and urinary retention are frequently observed side effects [30,37,38]. Salem et al reported that some women with epidural sufentanil analgesia during labor suffered severe nausea and pruritus drug administration [39]. We observed that women in group B1 experienced fewer side effects (nausea and urinary retention) following drug administration when compared with women in groups A and B2, with statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the inhibitory effects on cardiovascular and respiratory systems, sufentanil-induced gastrointestinal adverse effects, skin pruritus, and urinary retention are frequently observed side effects [30,37,38]. Salem et al reported that some women with epidural sufentanil analgesia during labor suffered severe nausea and pruritus drug administration [39]. We observed that women in group B1 experienced fewer side effects (nausea and urinary retention) following drug administration when compared with women in groups A and B2, with statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%